PENERAPAN FASE PRODUKSI TEKS EKSPOSISI PADA PEMBELAJARAN BERBASIS TEKS - Ellis Kurnia Utami (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
This study was conducted to describe the application of the production phase of exposition text, the difficulties encountered in the implementation phase of the production of texts exposition and strategies for resolving difficulties encountered in the implementation phase production exposition text in a text-based learning. This research data sourced from Indonesian teachers in class X MAN Babat Lamongan, Grade X IPA1 and exposition texts written by the students in groups and independent. The findings show that In the implementation phase of the production of texts exposition covers three stages, namely the planning stage in the form of lesson plans that have been created by teachers, the implementation phase which includes the activities of teachers and student activities, and assessment phase by evaluating the results of the product in the form of text exposition produced good students in groups or independently. The results showed the existence of difficulties in the implementation phase of the production of texts exposition comes from teachers and difficult student faced by teachers include adjusting format and systematics RPP, the selection of teaching methods, and the application of time allocation. Student difficulties include lack of student interest, difficulty communicating issues, and lack of learning resources.